AI-INTEGRATED DEEPIR MODEL-BASED STUDENT WORKSHEET: ENHANCING LEARNING OUTCOMES AND HOTS IN HIGHER EDUCATION - Budi Halomoan Siregar; Zul Amry; Kairuddin Kairuddin; Cut Latifah Zahari; Noorhelyna Razali (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to develop student worksheets (SW) by integrating Artificial Intelligence (AI) into the DEEPIR model, aligning with an outcome-oriented instructional framework to improve HOTS and learning products (innovative learning media and scientific publications).Methodology – This study employed a design research approach, implemented through three main stages: preparation and design, design experiment, and retrospective analysis. The research participants were 22 students of Mathematics Education enrolled in the Learning Media course. The research instruments included observation sheets, validation and practicality sheets, HOTS-based tests, and product assessment rubrics. Data were obtained through learning observations and analysis of the validity, practicality, effectiveness, and results of student products. All data were analyzed descriptively and inferentially to assess the quality of the student worksheets.Findings – The study's results demonstrate high levels of validity, practicality, and effectiveness. The n-gain value is 0.783 (high category). All students (100%) successfully produced innovative learning media products that met the criteria for content and pedagogical validity. In addition, 82% of students published scientific articles in nationally accredited journals with a minimum Sinta 4 rating. These findings indicate that AI-integrated DEEPIR-based student worksheets significantly improve HOTS and students' ability to produce media products and scientific articles.Contribution – This study produce a replicable model that educators can adapt to design learning instruments that foster cognitive engagement and academic products. Strategically, this study emphasizes the importance of adopting AI-based learning tools to strengthen the quality, relevance, and global competitiveness of higher education.